The application of the Spanish 'Tener verb' among Malay language speakers - Husain, Salina; Ismail, Muhd Zulkifli; Danuri, Norazmi (Hoehere Bundeslehranstalt und Bundesamt fuer Wein- und Obstbau, 2014)
This study focuses on the use of the Tener verb in teaching Spanish classes. The Tener verb is equivalent to has, have or, own. Because the verb has equivalent meaning in Malay, students are often confused to use this verb when it is used in different situations. The confusion occurs when students are unable to distinguish the form of the verb in Spanish compared to the Malay equivalent. Observations made on 30 respondents found that this confusion arises because students are not able to master certain forms of conjugating verbs in Spanish very well when translated from Malay language. Thus in accordance with the theory of Relevance (Sperber and Wilson, 1986 and 1995), where the authors try to compare the meaning of the verbs in search for answers to the confusion that exists. The findings demonstrate that despite having the same meaning, the functions of the verbs are different when translated into the target language. This study employs the translation methodology in the form of verb conjugation. The study is to see the similarities or differences of verb conjugation form- either they remain unchanged or have changed shape when translated from Malay to Spanish. Thus, the objective of this study is to identify students’ ability in applying Tener verb, and analyze the comparative verb form from the source language to the target language which is Spanish.